Propuesta para la mejora y reducción del tiempo empleado en el proceso de reclutamiento y selección de los perfiles tecnológicos de las empresas del portafolio de Hub, compañía del sector financiero y tecnológico de Latinoamérica - Avalos Lejabo, Angie Danitza (2022)
This work originates from the failures and discomforts reported by the teams involved in the recruitment processes focused on technology profiles, which are carried out in the Fintech companies in the portfolio of the company in question. Company whose identity will be protected, so from now on it will be called Hub, as well as the companies that are part of the Hub portfolio, called from now on as: Fintech A, Fintech B and Fintech C. All the information was collected through interviews with employees and interviews with technology profiles that have achieved or are currently participating in recruitment processes. Based on this information, in the first chapters of this work, the main discomforts related to recruitment processes focused on technology profiles are described, as well as the main problem that is defined. Next, in the continuous chapters, the solution to be implemented is determined. This solution proposes an improvement focused on the aspects of technology, processes and management, which are considered necessary to meet Hub's objectives, as it is responsible for the growth and strengthening of the value propositions of each Fintech that belongs to its investment portfolio. Finally, the financial evaluation of the project is detailed, which demonstrates the viability and approval of the project, as well as the final conclusions and recommendations.